Bioinformatic analysis of the RNA expression patterns in microgravity-induced bone loss - Zhang, Xiaoyan; Xue, Tong; Hu, Zebing; Guo, Xian; Li, Gaozhi; Wang, Yixuan; Zhang, Lijun; Xu, Liqun; Cao, Xinsheng; Zhang, Shu; Shi, Fei; Wang, Ke (Frontiers in Genetics, 2022)
Researchers have linked microgravity in space to the significant imbalance between bone formation and bone resorption that induces persistent bone loss in load-bearing bones. However, the underlying molecular mechanisms are still unclear, which constrains the development of therapeutic measures. The aim of this study was to identify hub genes and explore novel molecular mechanisms underlying microgravity-induced bone loss using transcriptome datasets obtained from the GEO and SRA databases. In summary, comparative RNA expression pattern studies that differ in species (Homo or Mus), models (in vitro or in vivo), microgravity conditions (real microgravity or ground-based simulators) and microgravity duration showed that it is difficult to reach a consistent conclusion about the pathogenesis of microgravity-induced bone loss across these studies. Even so, we identified 11 hub genes and some miRNA-mRNA interactions mainly based on the GSE100930 dataset. Also, the expression of CCL2, ICAM1, IGF1, miR-101-3p and miR-451a markedly changed under clinorotation-microgravity condition. These findings provide novel insights into the molecular mechanisms of bone loss during microgravity and could indicate potential targets for further countermeasures against this condition.